An MSRE-Assisted Glycerol-Enhanced RPA-CRISPR/Cas12a Method for Methylation Detection - Zhiquan Lu; Zilu Ye; Ping Li; Yike Jiang; Sanyang Han; Lan Ma (Biosensors)
Background: Nasopharyngeal carcinoma (NPC) is a malignant tumor with high prevalence in southern China. Aberrant DNA methylation, as a hallmark of cancer, is extensively present in NPC, the detection of which facilitates early diagnosis and prognostic improvement of NPC. Conventional methylation detection methods relying on bisulfite conversion have limitations such as time-consuming, complex processes and sample degradation; thus, a more rapid and efficient method is needed. Methods: We propose a novel DNA methylation assay based on methylation-sensitive restriction endonuclease (MSRE) HhaI digestion and Glycerol-enhanced recombinase polymerase amplification (RPA)-CRISPR/Cas12a detection (HGRC). MSRE has a fast digestion rate, and HhaI specifically cleaves unmethylated DNA at a specific locus, leaving the methylated target intact to trigger the downstream RPA-Cas12a detection step, generating a fluorescence signal. Moreover, the detection step was supplemented with glycerol for the separation of Cas12a-containing components and RPA- and template-containing components, which avoids over-consumption of the template and, thus, enhances the amplification efficiency and detection sensitivity. Results: The HGRC method exhibits excellent performance in the detection of a CNE2-specific methylation locus with a (limit of detection) LOD of 100 aM and a linear range of 100 aM to 100 fM. It also responds well to different methylation levels and is capable of distinguishing methylation levels as low as 0.1%. Moreover, this method can distinguish NPC cells from normal cells by detecting methylation in cellular genomes. This method provides a rapid and sensitive approach for NPC detection and also holds good application prospects for other cancers and diseases featuring DNA methylation as a biomarker.